The Effect of Joining Non-Formal Education and English Achievement - Sherly Marliasari; Riris Oktaviani (Channing : Journal of English Language Education and Literature, 2019)
The study aims to investigate the correlation between joining non-formal education and the English achievement of the second-grade students of SMA Negeri 2 Palembang. The problems of this study were: Is there any correlation between joining non-formal education and English achievement of the second-grade students of SMA Negeri 2 Palembang? And What does taking an English course gives impact toward English achievement of the second-grade students of SMA Negeri 2 Palembang? The method of this study used quantitative research. The total number of the sample was 52 students. The questionnaire and document were used to collect the data which were analyzed by using Pearson Product Moment correlation and Linear Regression analysis. The findings showed that: (1) there was a significant correlation between joining non-formal education and English achievement (r= .845), (2) there was a significant impact of taking English courses and students' English achievement (p-value= .000).